Ammonia borane-boron composites for hydrogen release: Thermolysis kinetics - Erguven, Hatice; Figen, Aysel Kanturk; Piskin, Sabriye (TAYLOR & FRANCIS INC, 2017)
In the present study, thermolysis characteristics and kinetics of ammonia borane-boron composites for hydrogen production were reported. Composites were prepared by ball milling neat ammonia borane with varying weight ratios of 20, 50, and 80 wt% of boron derivatives, namely boric acid and boron trioxide. Differential scanning calorimetry system was used to measure hydrogen production and determination of first hydrogen releasing temperature. Activation energy of composites decomposition was calculated by using several models, such as Kissinger, Ozawa-Flynn-Wall, and ASTM E 698 methods.
Keywords: Ammonia borane; boron; composites; hydrogen; kinetics; thermolysis; THERMAL-DECOMPOSITION; Energy & Fuels; Engineering; Environmental Sciences & Ecology